Hemorrhagic Bullous Henoch-Schönlein Purpura: Case Report and Review of the Literature - Nothhaft, Matthias; Klepper, Joerg; Kneitz, Hermann; Meyer, Thomas; Hamm, Henning; Morbach, Henner (Frontiers in Pediatrics, 2019)
Henoch-Schönlein Purpura (HSP) or IgA vasculitis is the most common systemic vasculitis of childhood and may affect skin, joints, gastrointestinal tract, and kidneys. Skin manifestations of HSP are characteristic and include a non-thrombocytopenic palpable purpura of the lower extremities and buttocks. Rarely, HSP may initially present as or evolve into hemorrhagic vesicles and bullae. We present an otherwise healthy 5-year-old boy with an acute papulovesicular rash of both legs and intermittent abdominal pain. After a few days the skin lesions rapidly evolved into palpable purpura and hemorrhagic bullous lesions of variable size and severe hemorrhagic HSP was suspected. A histological examination of a skin biopsy showed signs of a small vessel leukocytoclastic vasculitis limited to the upper dermis and direct immunofluorescence analysis revealed IgA deposits in vessel walls, compatible with HSP. To further characterize the clinical picture and treatment options of bullous HSP we performed an extensive literature research and identified 41 additional pediatric patients with bullous HSP. Two thirds of the reported patients were treated with systemic corticosteroids, however, up to 25% of the reported patients developed skin sequelae such as hyperpigmentation and/or scarring. The early use of systemic corticosteroids has been discussed controversially and suggested in some case series to be beneficial by reducing the extent of lesions and minimizing sequelae of disease. Our patient was treated with systemic corticosteroids tapered over 5 weeks. Fading of inflammation resulted in healing of most erosions, however, a deep necrosis developing from a large blister at the dorsum of the right foot persisted so that autologous skin transplantation was performed. Re-examination 11 months after disease onset showed complete clinical remission with re-epithelialization but also scarring of some affected areas.